Plasmid-DNA loaded chitosan microspheres for in vitro IL-2 expression - ÖZBAŞ, SUNA (ELSEVIER SCIENCE BV, 2004)
Interleukin-2 (IL-2) expression plasmid (pCXWN-hIL-2) loaded chitosan microspheres were evaluated for using in gene-based immumotherapy. Chitosan microspheres containing pCXWN-hIL-2 were prepared by using a precipitation technique. In addition, the effects of different factors such as the concentration (0.35-0.70%) and the molecular weight of chitosan (low and medium molecular weights), the plasmid amount (5-10 mug/ml) and the presence of glutaraldehyde during the encapsulation process, on microsphere characteristics were investigated. The size of microspheres changed between 1.45 and 2.00 mum. All the formulation factors affected the size of microspheres. The structure of plasmid remained unchanged during the encapsulation process and the release studies. Plasmid encapsulation efficiency of chitosan microspheres was high (82-92%). The zeta potential values of microspheres was approximately +5.2 to +12.4 mV. In vitro release properties of microspheres changed with formulation variables. In vitro release of DNA changed with the concentration and molecular weight of chitosan and initial plasmid amount. Addition of glutaraldehyde is not necessary for a formulation. MAT-LyLu, the rat prostate adenocarcinoma cell line, was used for the determination of the in vitro transfectional activity of IL-2 encoding plasmid DNA loaded chitosan microspheres and the level of IL-2 expressed into the cells was assayed using a ELISA kit. High level of IL-2 expression was obtained with plasmid-loaded chitosan microspheres. Microspheres showed similar IL-2 production as lipofectin. The molecular weight of chitosan used and the amount of plasmid influenced the in vitro IL-2 production in the cells. Encapsulation of IL-2 encoding gene into chitosan microspheres might be a useful strategy to increase the expression and to control the delivery of cytokine gene to cells. (C) 2004 Elsevier B.V. All rights reserved.
Keywords: interleukin-2; chitosan; microspheres; gene delivery; plasmid DNA; in vitro transfection; gene therapy; GENE DELIVERY; TRANSFECTION EFFICIENCY; INTERLEUKIN-2; NANOPARTICLES; NANOSPHERES; CANCER; MODEL